IMPLEMENTATION OF HEALTH PROTOCOL POLICIES IN TOURIST AREAS RUMAH SINGGAH TUAN KADI PEKANBARU DURING THE COVID-19 PANDEMIC - Rhestiwi Dhian Ramadhani; Andri Sulistyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Policy is an important part in an organization and government. The stages in making policy consist of planning, organizing, actuating, and controlling. This study aims to find out how the implementation of health protocol policies in tourist areas Rumah Singgah Tuan Kadi Pekanbaru during the covid-19 pandemic. This study uses a qualitative method with a descriptive approach. The data collection techniques used are observation, interviews and documentation. The key informants in this study were head of the arts and culture development division of the Pekanbaru city culture and tourism office, and the supporting informants were the management agency Rumah Singgah Tuan Kadi, visitors, the community and traders. Based on the results of the study, the authors concluded that the implementation of health protocol policies in tourist areas Rumah Singgah Tuan Kadi Pekanbaru during the covid-19 pandemic had gone well, visitors who came always implemented health protocols such as using masks, washing hands, and keeping a distance between visitors. In the management of a tourist attraction Rumah Singgah Tuan Kadi there are obstacles, namely the lack of funds, the funds used in the management of this tourist are funds originating from the Pekanbaru city culture and tourism office.   Keywords: Policy, Management, Tourist, Covid-19